Etiology of viral induced acute liver failure and defensins as potential therapeutic agents in ALF treatment - Hrynkiewicz, Rafał; Niedźwiedzka-Rystwej, Paulina (Frontiers in Immunology, 2023)
Acute liver failure (ALF) is a rare and severe disease, which, despite continuous advances in medicine, is still characterized by high mortality (65-85%). Very often, a liver transplant is the only effective treatment for ALF. Despite the implementation of prophylactic vaccinations in the world, the viral background of ALF is still a problem and leads to many deaths. Depending on the cause of ALF, it is sometimes possible to reverse this condition with appropriate therapies, which is why the search for effective antiviral agents seems to be a very desirable direction of research. Defensins, which are our natural antimicrobial peptides, have a very high potential to be used as therapeutic agents for infectious liver diseases. Unfortunately, conducting clinical trials for ALF is very difficult due to the severity of the disease and the low incidence, therefore animal models are important for the development of new therapeutic strategies. One of the best animal models that has real reference to research on acute liver failure (ALF) is rabbit hemorrhagic disease in rabbits caused by the Lagovirus europaeus virus. So far, there have been no studies on the potential of defensins in rabbits infected with Lagovirus europaeus virus.